Affective responses to and automatic affective valuations of physical activity: Fifty years of progress on the seminal question in exercise psychology. (May 2019) - Ekkekakis, Panteleimon; Brand, Ralf
Abstract: Objective: To critically review developments over the first fifty years of research (1967–2017) on (a) how people feel when they participate in exercise and physical activity, and (b) the implications of these responses for their willingness to become and remain active. Design: Non-systematic narrative review. Method: Representative sources were selected through a combination of computer searches and cross-referencing. Results: For over three decades, exercise psychology exhibited a fixation on the idea that exercise and physical activity make people feel better. This notion, however, seemed to contrast with evidence that most adults in industrialized countries exhibit low levels of activity. In the last two decades, a critical examination and overhaul of the methodological platform resulted in the delineation of a dose-response pattern that encompasses positive as well as negative affective responses, and revealed marked interindividual differences. An emerging literature is aimed at refining and testing integrative dual-process models that can offer specific predictions about the behaviors that may result from the interaction of automatic processes (theorized to be heavily influenced by past affective experiences) and deliberative processes (such as cognitive appraisals). Conclusions: Affective responses to exercise and physical activity are more complex than the long-popularized "feel-better" effect, encompassing both pleasant and unpleasant experiences and exhibiting marked interindividual variation. The potential of affective experiences to influence subsequent behavior offers an opportunity for an expanded theoretical perspective in exercise psychology. Highlights: Early studies yielded consistent support for an exercise-induced "feel better" effect. Methodological problems likely biased findings in favor of the "feel better" effect. The exercise-affect relation is complex, encompassing positive and negative effects. The "feel-better" effect is conditional rather than universal or automatic. Past affective responses may interact with reflective processes to influence behavior.